A systematic review of approaches to improve medication adherence in homeless adults with psychiatric disorders - Hird, Rachel; Radhakrishnan, Rajiv; Tsai, Jack (Frontiers in Psychiatry, 2024)
Introduction: Medication non-adherence is a significant problem among homeless individuals with psychiatric disorders in the United States. We conducted a systematic review to identify strategies to improve psychiatric medication adherence among homeless individuals with psychiatric disorders, including substance use disorders.Methods: We searched seven databases (MEDLINE, Embase, PsychInfo, Scopus, Web of Science, CDSR, and CENTRAL) and screened 664 studies by title and abstract followed by fulltext review. Our inclusion criteria were studies that: involved an intervention for homeless adults with psychiatric disorders, reported a quantitative outcome of medication adherence, and were published in English in a peer-reviewed journal. We rated the relative effectiveness of strategies described in each study using a self-designed scale.Results: Eleven peer-reviewed studies met criteria for inclusion in this review. Within these studies, there were seven different approaches to improve medication adherence in this population. Three studies were randomized controlled trials (RCTs) and the remaining were observational studies. Outpatient interventions included Assertive Community Treatment, Cell Phone-Assisted Monitoring, Customized Adherence Enhancement plus Long-Acting Injectable Medications, and Homeless-Designated Pharmacy Clinics. Residential, shelter-based, and inpatient interventions included use of the Housing First model, Modified Therapeutic Communities, and Homeless-Designated Inpatient Care. The approaches described in four of the eleven studies were rated as scoring a 3 or higher on a 5-point scale of effectiveness in improving medication adherence; none received 5 points.Discussion: The interventions with the strongest evidence for improving medication adherence in this population were Assertive Community Treatment, Customized Adherence Enhancement plus Long-Acting Injectable Medications, and Housing First. Overall, studies on this topic required more rigor and focus on medication adherence as an outcome in this population. This review highlights several promising strategies and the need for larger RCTs to determine effective and diverse ways to improve medication adherence among homeless adults with psychiatric disorders.